Historia oral e historias de vida en el campo - María Teresa Quinto (Estudios sobre las Culturas Contemporáneas)
In this methodological article the author argues, on the basis of her experience in studying systematically sugar can agriculture in some areas of Mexico -Veracruz, Colima, Michoacan and Jalisco- that she arrived at the conclusion that this activity, along with production, cultural work, pay and asymmetric social relations, constituted the central axis of one more subculture in the Mexican countryside. It considers a subculture defined by production complexes where the type of cultivation, credit and the social relations of production constitute a form of social production and reproduction. The article understands that culture is in the minds of individuals, and individual minds are in culture, such that the actors and/or social subjects become transformed into units of analysis - elementary for understanding, analyzing, explicating, interpreting and understanding - for the study of sugar cane culture in particular.